Improving Mathematics Learning Outcomes in Addition and Subtraction Through the Direct Instruction Model among Third-Grade Elementary School Students - Nuhaa Adani Pitron; Nuralfia Sauhana; Alya Shalsa Redina; Adinda Nur Fajriyanti; Mawardi Mawardi (Indonesian Journal Publisher, 2026)
This study aimed to improve third-grade students’ mathematics learning outcomes in addition and subtraction through the Direct Instruction model. The study employed classroom action research conducted in two cycles, each consisting of two meetings, with 10 third-grade students at an elementary school in Tangerang, Indonesia. Because no formal minimum mastery criterion was specified in the available research record, action success was operationally defined as a marked increase in the class mean together with improvement in student and teacher observation scores in Cycle II. Data were collected using cycle-end evaluation tests, student activity observation sheets, teacher instruction observation sheets, and field notes. The data were analyzed descriptively by comparing class means and observation scores across cycles and interpreting changes recorded in the field notes. The mean evaluation score increased from 54 in Cycle I to 94 in Cycle II, representing a 40-point increase. Student observation scores increased from 60 to 74, while teacher observation scores increased from 69 to 87. Cycle II refinements included animated PowerPoint media, contextual problems, gradual guided practice, immediate feedback, and targeted assistance for students who experienced difficulty. The results indicate a marked improvement within the classroom studied. However, the findings should be interpreted within the limits of the small sample, short duration, absence of a comparison group, and incomplete student-level and instrument documentation.